Activating the pregnane X receptor by imperatorin attenuates dextran sulphate sodium‐induced colitis in mice. (23rd July 2018) - Liu, Meijing; Zhang, Guohui; Zheng, Chunge; Song, Meng; Liu, Fangle; Huang, Xiaotao; Bai, Shasha; Huang, Xinan; Lin, Chaozhan; Zhu, Chenchen; Hu, Yingjie; Mi, Suiqing; et al.
Abstract : Background and Purpose: Activation of the human pregnane X receptor (PXR; NR1I2) has potential therapeutic uses for inflammatory bowel disease (IBD). Imperatorin (IMP), a naturally occurring coumarin, is the main bioactive ingredient of Angelica dahurica Radix, which is regularly used to treat the common cold and intestinal disorders. However, there are no data on the protective effects of IMP against IBD. Experimental Approach: The effects of IMP on PXR‐modulated cytochrome P450 3A4 (CYP3A4) expression were assessed using a PXR transactivation assay, a mammalian two‐hybrid assay, a competitive ligand‐binding assay, analysis of CYP3A4 mRNA and protein expression levels and measurement of CYP3A4 activity using a cell‐based reporter gene assay and in vitro model. The inhibitory effects of IMP on NF‐κB activity were evaluated by a reporter assay and NF‐κB p65 nuclear translocation. The anti‐IBD effects of IMP were investigated in a dextran sulphate sodium (DSS)‐induced colitis mouse model. Colon inflammatory cytokines were assessed byelisa . Key Results: IMP activated CYP3A4 promoter activity, recruited steroid receptor coactivator 1 to the ligand‐binding domain of PXR and increased the expression and activity of CYP3A4 . PXR knockdown substantially reduced IMP‐induced increase in CYP3A4 expression. Furthermore, IMP‐mediated PXR activation suppressed the nuclear translocation of NF‐κB and down‐regulated LPS‐induced expression of pro‐inflammatory genes. Nevertheless, PXR knockdown partially reduced the IMP‐mediated inhibition of NF‐κB. IMP ameliorated DSS‐induced colitis by PXR/NF‐κB signalling. Conclusions and Implications: IMP acts as a PXR agonist to attenuate DSS‐induced colitis by suppression of the NF‐κB‐mediated pro‐inflammatory response in a PXR/NF‐κB‐dependent manner.